Prototipe Komik Hadis sebagai Media Pembelajaran Hadis: Studi Hadis tentang Ukhuwah - Muhammad Iqbal As Sidiq (UIN Sunan Gunung Djati Bandung, 2026)
This research was conducted based on the urgency of hadith learning for society, the low interest in reading in Indonesia, and the lack of understanding of ukhuwah in society. Therefore, the author initiated the development of an enjoyable and easy-to-understand hadith learning medium in the form of a comic. The objectives of this research are to produce a prototype of a hadith comic about ukhuwah, identify the media and production process involved, and identify the hadiths used in the comic. The method employed in this research is qualitative research using a literature study approach. The production of the hadith comic prototype utilized several supporting media, including Al-Manshah Al-Hadisiyah, Google Scholar, Microsoft Word, and Clip Studio Paint. The production process consisted of several stages: searching for relevant hadiths and data, recording and writing the substance, designing the comic, and conducting an evaluation. The hadith comic prototype consists of six chapters containing eight hadiths as its main content. Subsequently, the prototype was further developed and registered for an ISBN under the title “Qola, Rapatkan Saf Kukuhkan Ukhuwah.” This research still has limitations, particularly in terms of the comprehensiveness of the discussion presented.